DAILY LIVES OF CIRCASSIANS IN CONFLICT-AFFECTED SITUATIONS: ETHNOGRAPHY OF DEATH - M. A. TEKUEVA; E. A. NALCHIKOVA; A. A. KONOVALOV; M. Kh. GUGOVA (Кавказология, 2019)
The current paper studies mental relations among Circassians towards death and their manifestations in day-to-day routines. The Caucasian war (1763-1864) constitutes the historical background for the research as a chronological milestone saturated with dramatic historical events and cultural landmarks representing ethnic distinctiveness. The paper is based on narrative, folklore, and ethnographical sources. The research methodology involves modern scholar approaches, i.e. everyday history (Alltagsgeschichte), gender history, and history of mentality. Implementation of these toolkits reveals behavioral drives in the face of death, perception of death amongst a conflict: sense of alarm, fearlessness, mental changes. Circassians within this framework do not merely portray an abstract party to a conflict, but historic subject. Not only battles, victories and defeats the Caucasian war embodies, but also it incorporated fortunes, feats and betrayals, laments and memorial song. On the one hand, a war transforms death into the routine, on the other hand, it elevates personal experiences up to the national tragedies. Authors emphasized two contrasting tendencies in the development of traditional ritual patterns: their cultivation amidst tedious military confrontation and erosion of traditional culture as a result of colonization of the North Caucasus. The article considers women’s attitudes towards wartime losses (distress, sacrifice, perseverance, ritual execution) ant their role in forming men’s spirit of resistance (mechanisms of psychological exposure), and attitudes among Circassians towards their died fellows on the battlefield. Ethnography of death and its study conclude into recognition of the value of ritual culture and semantic text that translated indigenous cultural values to descendants.